Cost-Effectiveness of Cilostazol, Naftidrofuryl Oxalate, and Pentoxifylline for the Treatment of Intermittent Claudication in People With Peripheral Arterial Disease. (March 2014) - Meng, Yang; Squires, Hazel; Stevens, John W.; Simpson, Emma; Harnan, Sue; Thomas, Steve; Michaels, Jonathan; Stansby, Gerard; O'Donnell, Mark E.
We assessed the cost-effectiveness of cilostazol, naftidrofuryl oxalate, and pentoxifylline for intermittent claudication due to peripheral arterial disease (PAD) in adults whose symptoms continue despite a period of conventional management. A Markov decision model was developed to assess the lifetime costs and benefits of each vasoactive drug compared to no vasoactive drug and with each other. Regression analysis was undertaken to model the relationship between maximum walking distance and utility. Resource use data were sourced from the literature and sensitivity analyses were undertaken. Naftidrofuryl oxalate is more effective and less costly than cilostazol and pentoxifylline and has an estimated cost per quality-adjusted life year gained of around £6070 compared to no vasoactive drug. The analysis uses effectiveness evidence from a network meta-analysis. In contrast to previous guidelines recommending cilostazol, the analysis suggests that naftidrofuryl oxalate is the only vasoactive drug for PAD which is likely to be cost-effective.